Physicians' Biological Drug Preference in Patients With Rheumatoid Arthritis and Spondyloarthritis With a History of Malignancy: Perspectives From the Treasure Database. Issue 2 (March 2022) - Tekgoz, Emre; Colak, Seda; Yardimci, Kubra G.; Kucuksahin, Orhan; Cinar, Muhammet; Yilmaz, Sedat; Kasifoglu, Timucin; Bes, Cemal; Yagiz, Burcu; Erden, Abdulsamet; Kilic, Levent; Kanitez, Nilufer A.; et al.
Abstract : Objective: Because of concerns about malignancy risks, using biological disease-modifying antirheumatic drugs (bDMARDs) in patients with a history of malignancy remains a challenging issue in rheumatology practice. This study aimed to investigate bDMARD preferences of physicians when treating of rheumatoid arthritis (RA) and spondyloarthritis (SpA) patients with a history of malignancy. Methods: The data for this cross-sectional study were gathered from the TReasure database using a date range of December 2017 and January 2020. Biological disease-modifying antirheumatic drug preferences were analyzed for 40 RA patients and 25 SpA patients with a history of malignancy. Results: The most frequently prescribed bDMARD was rituximab, which was given to 28 RA patients (70%). For 25 patients (62.5%), the time between the diagnosis of malignancy and starting on a bDMARD regimen was less than 60 months, with a median interval of 43.5 months. Among SpA patients, the preferred bDMARDs were secukinumab and etanercept, which were each administered to 7 patients (28%). For 13 SpA patients (52%), the time between the diagnosis of malignancy and starting on bDMARDs was less than 60 months, with a median interval of 97 months. Conclusions: The observed bDMARD preferences may be related to the therapeutic effects of rituximab on lymphoproliferative malignancies, the protective effects of secukinumab on tumor progression, and the short half-life of etanercept. Biological disease-modifying antirheumatic drugs should be used in RA and SpA patients with malignancy in case of high inflammatory activity.